Biomimetic Superhydrophobic Materials Construct from Binary Structure: A Review on Design, Properties, and Applications - Jiahao Li; Zhiguang Guo; Weimin Liu (Advanced Materials Interfaces, 2023)
Abstract In recent decades, the development of biomimetic superhydrophobic surface structures has allowed several properties of superhydrophobic materials to be increasingly developed. This review addresses mainly three aspects. First, two kinds of structures with superhydrophobic properties: binary structures and unitary structures, are analyzed and compared. The binary structure, which includes micro‐ and nanostructures, is responsible for the development of superhydrophobicity in most natural creatures and artificial materials. And hierarchical binary structures, which combine micro‐ and nanoscale structures, actually perform better at superhydrophobic. Second, various properties of superhydrophobic materials achieved through binary structures, including self‐cleaning, antireflection, drag‐reduction, and mechanically robust and durable superhydrophobic surfaces are summarized. Each structure possesses both superiority and vulnerability. The combination of various structures can help develop adaptable and practical materials. Finally, the combinations of different properties in superhydrophobic via using a binary structure are enumerated. Materials with various properties can adapt to different working environments.